INTENSI MEMILIH MAHASISWA DALAM PEMILIHAN KEPALA DAERAH (PILKADA) TAHUN 2015 DITINJAU DARI POLA ASUH DEMOKRATIS ORANG TUA DAN KONFORMITAS TEMAN SEBAYA - Lusia Astrika (Program Studi Sarjana (S1) Ilmu Pemerintahan, FISIP, Universitas Diponegoro, 2016)
Political Socialization is the process of obtaining a person's attitude and orientation towards political phenomena which are generally applicable in the community where it is located. Political socialization received individual will also affect the intention or the intention to participate in politics. Two agents in political socialization plays an important role especially for first-time voters are agents of family and peers. In the family, took parenting parents against children, and the ongoing process of peer friendship conformity.Based on the research conducted, there is simultaneously a significant relationship between democratic parenting style of parents and peer conformity to the intention pick on students in elections 2015. The democratic parenting parents positively and significantly related to the intention pick on students in election 2015, (sig. 0.008 <0.05) where more democratic parenting parents (positive), the greater the intention of selecting students in the elections of 2015. Conformity peers positively and significantly related to the intention pick on students in the elections of 2015 (sig. 0.012 <0.05), where the greater conformity peers, the greater the intention of selecting students in elections 2015.Cultural discussion and sharing is done with the parents and with peers are expected to be able to establish the mindset of students in a more rational in terms of choosing. So this will increase the intention to memlih. Not on the basis of follow - follow-up alone, but for their consciousness to be intelligent and rational voters, so that it can account for the results of his own choice.